Taxonomic structure and variability of Selenocephalus obsoletus (Germar, 1817) (Auchenorrhyncha: Cicadellidae: Deltocephalinae: Selenocephalini) - Tishechkin, Dmitri Yu. (Zootaxa, 2019)
Comparative investigation of morphology and calling signals of Selenocephalus obsoletus (Germar, 1817) from different localities in Western Europe, Bulgaria, Ukraine, and Russia showed that this species includes two subspecies. S. obsoletus obsoletus occurs in the Mediterranean, S. obsoletus rossicus Zachvatkin, 1945, stat. n. is distributed from the steppes of Eastern Europe up to Bulgaria; the boundary between two subspecies in the Balkans coincides with the boundary of the Mediterranean Region. Lectotypes of Selenocephalus rossicus Zachvatkin, 1945 and Selenocephalus rossicus tesquicola Zachvatkin, 1945 are designated; the synonymy S. obsoletus rossicus = S. rossicus tesquicola syn. n. is established.